Abstract 034: Value of Immediate Flat Panel Perfusion Imaging After Endovascular Therapy: A proof of concept study - Adnan Mujanovic; Christoph Kurmann; Michael Manhart; Eike Piechowiak; Sara Pilgram‐Pastor; Bettina Serrallach; Gregoire Boulouis; Thomas Meinel; David Seiffge; Simon Jung; Marcel Arnold; Thanh Nguyen; et al. (Stroke: Vascular and Interventional Neurology)
Introduction Clinical utility and diagnostic sensitivity of new‐generation flat‐panel computed tomography perfusion imaging (FPCTP) performed immediately after mechanical thrombectomy (MT) is unknown. We aimed to assess whether FPCTP obtained directly after MT could provide additional potentially relevant information on tissue reperfusion status. Methods Qualitative, single‐center analysis of all consecutive acute stroke patients admitted between 06/2019 and 03/2021 who underwent MT and post‐interventional FPCTP (n=26). A core‐lab blinded to technical details and clinical data performed reperfusion grading on post‐interventional digital subtraction angiography (DSA) images and time‐sensitive FPCTP maps. All patients were classified according to agreement between DSA and FPCTP. Results In 10/26 patients FPCTP revealed new, potentially clinically relevant information. Core‐lab adjudicated dichotomized detection of hypoperfusion (present/absent) was concurring in 21/26 (81%) patients. Of these, reperfusion findings showed perfect agreement on location and size in 16 (62%) patients, while in 5 (19%) patients with incomplete reperfusion, FPCTP showed additional hypoperfused areas missed on DSA. Of the remaining five patients subject to disagreement regarding the presence or absence of hypoperfusion, three showed complete reperfusion on DSA but hypoperfusion was noted on FPCTP, whereas two showed incomplete reperfusion on DSA without detectable hypoperfusion on FPCTP. FPCTP findings could have avoided Thrombolysis in Cerebral Infarction (TICI) overestimation in all false‐positive operator‐rated TICI3 cases. Conclusion In both core‐lab and real‐world operator assessment, FPCTP may provide additional clinically relevant information in a considerable percentage of patients undergoing MT. Hence, FPCTP may constitute a new standard for evaluating reperfusion efficacy and informed decision making in the angiography suite.